Meningkatkan Kemampuan Matematika Siswa Kelas I dengan Menggunakan Media Pembelajaran Sempoa di SDN 17/I Rantau Puri - Sari, Ria Puspita; Ardiansyah, Ferdy; Salsabilla, Shella; Hidayati, Isna Wahyu (TSAQOFAH, 2023)
The reason mathematics is considered an important subject is because mathematics is able to equip students to think logically and analyze. The purpose of this study was to improve the math skills of grade 3 students at SDN 17/I Rantau Puri by using the abacus media. The research method used is Classroom Action Research (CAR). The research subjects were grade 3 SDN 17/I Rantau Puri with observation, interview and documentation data collection techniques involving class teachers and grade 3 students. The research process was passed through Cycle I and Cycle II with components namely planning, action, observation, and reflection. From the results of this study, we can see that using Sempoa media can improve math skills in grade 3 students at SDN 17/I Rantau Suri. This can be seen from the teacher's activities which were initially in the sufficient and good category in cycle I so that they received a very good category in cycle II. While student activity also increased with the very good category.